Understanding chimpanzee facial expression: insights into the evolution of communication - Parr, Lisa A. (Oxford University Press, 2006)
To understand the evolution of emotional communication, comparative research on facial expression similarities between humans and related species is essential. Chimpanzees display a complex, flexible facial expression repertoire with many physical and functional similarities to humans. This paper reviews what is known about these facial expression repertoires, discusses the importance of social organization in understanding the meaning of different expressions, and introduces a new coding system, the ChimpFACS, and describes how it can be used to determine homologies between human and chimpanzee facial expressions. Finally, it reviews previous studies on the categorization of facial expressions by chimpanzees using computerized tasks, and discusses the importance of configural processing for this skill in both humans and chimpanzees. Future directions for understanding the evolution of emotional communication will include studies on the social function of facial expressions in ongoing social interactions, the development of facial expression communication and more studies that examine the perception of these important social signals.